Еколого-географічний аналіз бальнеологічного курорту Східниця = Ecology-geographical analysis of the Skhidnytsia balneological resort - Holovatyi, Marian (Journal of Education, Health and Sport, 2016)
Holovatyi Marian. Еколого-географічний аналіз бальнеологічного курорту Східниця = Ecology-geographical analysis of the Skhidnytsia balneological resort. Journal of Education, Health and Sport. 2016;6(1):85-92. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44645 http://ojs.ukw.edu.pl/index.php/johs/article/view/44645 http://pbn.nauka.gov.pl/works/692587 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016. Еколого-географічний аналіз бальнеологічного курорту Східниця Ecology-geographical analysis of the Skhidnytsia balneological resort Мар’ян Головатий, аспірант географічного факультету Львівського національного університету імені Івана Франка Marian Holovatyi, Ivan Franko National University of Lviv, postgraduate student Ключові слова: еколого-географічний аналіз, екологічний паспорт, бальнеологічний курорт, мінеральні води. Key words: balneological resort, еcology-geographical analysis, environmental passport, mineral waters. Анотація. Проведено еколого-географічний аналіз бальнеологічного курорту Східниця на основі екологічного паспорту, що розроблений відповідно до специфіки бальнеологічних курортів та заповнений за результатами польових досліджень, статистичних та фондових матеріалів. Виокремлено існуючі переваги та загрози у функціонуванні курорту. Здійснено оцінку еколого-географічної ситуації курорту. Abstract. Ecology-geographical analysis of the Skhidnytsia balneological resort was accomplished based on ecological passport, which is developed according to the specific character of balneological resorts and filled with results data of field research, statistical and stock materials. Existing benefits and threats in the resort operation were determined. Ecology-geographical situation of the Skidnytsia resort was evaluated.